Descriptive Study On Teaching-Learning Process Of Reading At The Seventh Grade Of SMP Muhammadiyah 8 Surakarta In 2014/2015 Academic Year - Sholikah, Indah Maratus; , Aryati Prasetyarini, S.Pd., M.Pd; , Siti Fatimah, S.Pd., H.Hum (2015)
This study focuses on reading teaching-learning process at the seventh grade of SMP Muhammadiyah 8 Surakarta. This study is aimed at describing the teaching objective, curriculum, syllabus, the roles of the teacher, the roles of the students, material, the techniques, the procedures of teaching-learning process of reading, the evaluation, and problem faced in teaching-learning process of reading. This study was an ethnography research. The subject of the study was the seventh grade students of SMP Muhammadiyah 8 Surakarta which consists of 23 students. The methods of collecting data were observation, interview, and document analysis. In analyzing data, the writer used an interactive model. Based on the research finding, the objective of teaching in SMP Muhammadiyah 8 Surakarta was to develop the students' reading ability, particularly to enrich their vocabulary and the students understanding in the content and the meaning of the text. The curriculum was the 2013 Curriculum. The syllabus had been prepared and determined by the central government. The teacher's roles were as a monitor, model, organizer, controller, counselor, and evaluator. The students' roles were as listener and performer. The material used in reading teaching-learning process were taken from books. The teacher used several techniques, namely: question and answer, translation, games, and reading aloud. The English teacher applied two approaches, namely: bottom-up and topdown. The teacher taught reading using some procedures like: observing, questioning, collecting information or experimenting, associating or information processing, and communicating. In SMP Muhammadiyah 8 Surakarta, the English teacher used daily test, mid test, and final test as the evaluation. The writer also finds problems faced by the teacher in which students got difficulties in understanding the text, few students cannot put themselves in the right time and the right place, and each student's different capability. And the problems faced by the students were low motivation, limited vocabulary, and not knowing the content of text.